Muerte del cuerpo político. Sensibilidad y racionalización de los republicanos mexicanos 1820. - Alicia Tecuanhuey Sandoval (Centre de Recherches sur les Mondes Américains, 2008)
The metaphor, the Death of the Political Body, appeared in one of the first poblano imprints. It had a polemic reception because it was used to characterize the crisis of the Spanish monarchy and its constitutional solution. Those who defended its pertinence for the Spanish case, sought to make visible the revolutionary and founding character of the Spanish constitution of 1812. Emotions and feelings were hidden behind concepts and rationalizations. I analyze in this paper some writings from 1820 onwards, to understand those intellectual activities, and their emotional background.